Shared Histories, Personalities, Traditions. European Examples (Annual of the Faculty of Philosophy in Skopje, 2018)
The purpose of this paper is to show the role of the common past in the emergenceand development of some smaller European nations. Shared past in the Balkans is seen solelythrough the prism of nationalism. When someone talks about a shared history, he does itin order to show that the others in that history have no past. There are several examples ofshared history worldwide and it is normally not a problem, except in our region. Also, therole of a person in the past of two or more nations is very common and it should not be aground for misunderstanding and conflict. Fluidity of ethnic identity is not associated onlywith the Balkans; it is also present in some other European countries. Such is the case, forexample, with Lithuania. In addition, when it comes to the role of reformers and intellectualswho had different ethnic backgrounds in the emergence and development of some modernEuropean nations, we may observe that there are such examples, for instance, in Finlandand Estonia. Unlike the Balkans, shared histories, common personalities and intellectualswho had different ethnic backgrounds in terms of nations where they contributed greatly,in some European countries it does not mean denial of the right to self-determinationand existence.
Keywords: PERSON; NATION; SLOVAKIA; FINLAND; ESTONIA; NORWAY